Protection of EU financial interests: EPPO’s cooperation with non-EU states - Marina Matić Bošković (Revija za kriminologiju i krivično pravo)
The European Public Prosecutor’s Office (EEPO) is a cornerstone institution in the EU’s efforts to combat financial crimes and protect its financial interests. Its role encompasses a wide range of activities, from investigating and prosecuting financial crimes to fostering cooperation and ensuring accountability. By centralizing and coordinating efforts across member states, the EPPO significantly strengthens the EU’s ability to safeguard its financial resources and uphold the rule of law. The cooperation between the EPPO and non-EU countries, particularly candidate countries, is essential for ensuring comprehensive protection against financial crimes due to their economic ties with the EU. Sebia, as candidate country for EU membership, has a vested interest in aligning its judicial and law enforcement practices and regulations with the European Union. For the period 2021-2023, Serbia has been allocated 571 million euro under the IPA III funding for national programmes. Proper utilization and protection of these funds are vital, and cooperation with the EPPO can help in achieving this objective. Through mutual legal assistance, information sharing, capacity building, joint investigations, and preventive measures, this international collaboration is safeguarding the EU’s financial stability. The paper identifies benefits and challenges of cooperation between third countries national authorities and EPPO. The paper recognizes challenges in identification of the legal basis for cooperation with the EPPO for some of the third countries and propose options for overcoming and mitigation measures.